2021
DOI: 10.1101/2021.12.17.21267362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of airborne transmission in a large single source outbreak of SARS-CoV-2 in a Belgian nursing home in 2020

Abstract: Objectives: To better understand the conditions which have led to one of the largest COVID-19 outbreaks in Belgian nursing homes in 2020. Setting: A nursing home in Flanders, Belgium, which experienced a massive outbreak of COVID-19 after a cultural event. An external volunteer who dressed as a legendary figure visited consecutively the 4 living units and tested positive for SARS-CoV-2 the next day. Within days, residents started to display symptoms and the outbreak spread rapidly within the nursing home. Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Shared rooms require patients to eat and drink in the same room under limited ventilation or aeration, so such hospital environmental factors that are difficult to prevent may have contributed to the spread. Some studies have shown that airborne transmission can occur in specific circumstances (5,6). Before and during the cluster, no patients received aerosol-generating procedures, including endotracheal intubation or high-flow nasal cannula oxygen or standard oxygen therapy (7).…”
Section: Discussionmentioning
confidence: 99%
“…Shared rooms require patients to eat and drink in the same room under limited ventilation or aeration, so such hospital environmental factors that are difficult to prevent may have contributed to the spread. Some studies have shown that airborne transmission can occur in specific circumstances (5,6). Before and during the cluster, no patients received aerosol-generating procedures, including endotracheal intubation or high-flow nasal cannula oxygen or standard oxygen therapy (7).…”
Section: Discussionmentioning
confidence: 99%